MEOP-CTD in-situ data collection: a Southern ocean Marine-mammals calibrated sea water temperatures and salinities observations - Kovacs, Kit M.; Fedak, Micheal; Lydersen, Christian; Nøst, Ole Anders; Biuw, Martin; Roquet, Fabien (SEANOE, 2009)
Within the Marine Mammals Exploring the Oceans Pole to Pole (MEOP) program, several international teams agreed to share their CTD-SRDL data sets to produce a single, uniformly calibrated, homogeneous database of hydrographic profiles. Here we present the MEOP-CTD database, a quality-controlled collection of most seal-derived hydrographic data obtained in the period 2004–2010. The MEOP-CTD database includes 349 CTD-SRDLs, representing 165,000 TS profiles. The majority of loggers were deployed on elephant seals, with a lesser number on Weddell and crabeater seals. On average, profiles are 500 m deep, although some seals occasionally reach 2000 m or more. The MEOP-CTD collection of profiles produces near circumpolar coverage, although some regions such as the Weddell and Ross Seas remain poorly sampled. More than 60% of TS profiles were obtained south of the southern limit of the ACC, where few Argo data exist. The migration distance of seals depends highly on the deployment location and time of the year, ranging from 100 km to more than 5000 km, while the life span of a CTD-SRDL varies from 1 to 10 months (5 months on average). The bulk of measurements were made in the austral autumn and winter, when other in situ data are scarce, yielding hydrographic sections with high spatial and temporal resolution (2.5 profiles per day on average).